GENDER BASED DISTRIBUTION AND CLINICAL PRESENTATION OF ACUTE CHOLECYSTITIS PATIENTS AT A TERTIARY CARE HOSPITAL (The Research of Medical Science Review, 2025)
OBJECTIVE: This study aims to identify the frequency of acute cholecystitis across genders and analyze the respective clinical presentation in adults within a tertiary care hospital setting.METHODOLOGY: A descriptive cross-sectional study was performed from 2024 to 2025 at Abbasi Shaheed Hospital Karachi to assess gender-based difference in the clinical presentation of acute cholecystitis. A consecutive non-probability sampling method was used to include adult patients aged 18 years and above with symptoms of acute cholecystitis who presented within 48 hours of the onset of symptoms. Statistical analysis of data related to demographics, clinical features, laboratory parameters and ultrasound findings was done using SPSS version 26. Statistical significance was set at p ≤ 0.05.RESULT: Among 79 patients, 48 (60.8%) were female and 31 (39.2%) male, with a mean age of 52.65 ± 13.98 years. Acute cholecystitis was diagnosed in 22 patients (27.8%). Right upper quadrant pain (83.5%), nausea/vomiting (74.7%), and Murphy’s sign (67.1%) were most common. No statistically significant gender-based differences were found in symptoms, comorbidities, or ultrasound findings among patients with acute cholecystitis (p > 0.05).CONCLUSION: The research indicates that while the prevalence of gallbladder disease was notably higher among females, males exhibited a greater proportion of diagnoses pertaining to acute cholecystitis. Clinical manifestations including right upper quadrant discomfort, nausea and vomiting, as well as the presence of Murphy’s sign were prevalent in both sexes. Nevertheless, no statistically significant gender-related disparities were detected in the clinical presentation, underscoring the necessity for the establishment of standardized diagnostic protocols irrespective of gender in cases of suspected acute cholecystitis.